2020
DOI: 10.3389/fneur.2020.00259
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Cardio-Cerebrovascular Risk Factors for Benign Paroxysmal Positional Vertigo

Abstract: Background: Benign paroxysmal positional vertigo (BPPV) is the most common cause of vertigo, especially in the elderly. Several studies have revealed a possible seasonality to BPPV. However, whether the seasonality of BPPV also exists in China is unclear. The characteristics of cardio-cerebrovascular risk factors for BPPV in the cold season have not yet been investigated. Objectives: (1) To investigate the seasonality of BPPV; (2) To explore the relationship between cardio-cerebrovascular risk factors and seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Our study shows HC-BPPV recurrence is not correlated with age, gender, seasons, and blood pressure status, which is consistent with some previous studies (21)(22)(23), while other studies presented conflicting results, including our previous study on PC-BPPV (16). The results also showed that the recurrence of BPPV was closely associated with the female gender.…”
Section: Hc-bppv Recurrence and Risk Factorssupporting
confidence: 90%
“…Our study shows HC-BPPV recurrence is not correlated with age, gender, seasons, and blood pressure status, which is consistent with some previous studies (21)(22)(23), while other studies presented conflicting results, including our previous study on PC-BPPV (16). The results also showed that the recurrence of BPPV was closely associated with the female gender.…”
Section: Hc-bppv Recurrence and Risk Factorssupporting
confidence: 90%
“…The inner ear is an organ with strong aerobic metabolism and is sensitive to ischemia [9,23]. In particular, ischemia can cause local microcirculation disturbances to the vestibule, damage the elliptic sac, make otoliths more likely to fall off, and at the same time, affect the absorption of otoliths in the endolymph, which causes BPPV recurrence and occurrence of RD [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The labyrinthine artery of the inner ear is a tiny terminal artery. Small vessel lesions that directly damage the tiny arteries of the inner ear lead to microcirculation disorders, which can cause damage to the blood Ivyspring International Publisher supply vessels of the inner ear, leading to the shedding of otoliths, which may be involved in BPPV pathogenesis [7][8][9]. Abnormal cerebral small vessels, including arterioles, branch arterioles, capillaries and venules, can directly damage blood supply, leading to microcirculatory disorders [10].…”
Section: Introductionmentioning
confidence: 99%
“…The median number of BPPV patients, median sunshine hours per month, horizontal solar irradiance, and other climatic variations are described and demonstrate no statistical significance between the month of BPPV onset and months with low serum Vitamin D levels (Figures 2 and 3). Several studies mention the statistically significant difference between the incidence of BPPV in months when Vitamin D levels are lower compared to those months that these levels are higher while others report on specific atmospheric data such as barometric pressure and its possible relationship with BPPV [5][6][7][15][16][17]. On the other hand, recent studies report no seasonality in BPPV patients [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies mention the statistically significant difference between the incidence of BPPV in months when Vitamin D levels are lower compared to those months that these levels are higher while others report on specific atmospheric data such as barometric pressure and its possible relationship with BPPV [ 5 - 7 , 15 - 17 ]. On the other hand, recent studies report no seasonality in BPPV patients [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%